Paoay kumakaway a textual analysis on the media coverage of the travel and tourism program of Ilocos Norte from July 2010 to July 2012 - Cachero,Ellouise Limguangco; Calucag, Ma. Krizzia Abigail M.; Rara, Maria Christina Imperial; University of the Philippines. College of Mass Communication (2013)
"This study examined how news and feature reports of national (Inquirer.net, Philstar.com, Rappler.com and Interaksyon.com) and local (Ilocostimes.com and Ilocossentinel.com) news portals framed the new travel and tourism branding of the Provincial Government of Ilocos Norte (PGIN), known as "Paoay Kimakaway", from July 2010 to July 2012. Textual analysis and integrated framework of POlitical Economic Media Theory and Framing Theory were utilized to study the angle, focus and content of the published news articles. Interviews with people of relevant expertise were conducted to gain sights for the chosen research. Majority of the published news reports were framed in a manner that exhibited partiality to PGIN, specifically on its governor, Maria Imelda Josefa "Imee" marcos. The news organizations contributed mainly for the publicity and promotion for Ilocos Norte. It was also determined that contents of news reports were affected by commercial and political pressures. The researchers also realized that despite the great efforts of PGIN to attract media attention, they do not have a systematize way of tracking reports written for and about them, defining the purpose of gaining media mileage as truth and accuracy is not properly monitored."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Advertising -- Tourism -- Philippines -- Ilocos Norte; Branding (Marketing).; Journalism -- Objectivity; Philippines -- Ilocos Norte -- Press coverage